Enhancing PAI teacher professionalism through PPG implementation at SD Negeri 2 Tragan, Temanggung - Prisa Widya Indarni Masfufah; Sigit Tri Utomo; Ana Sofiyatul Azizah; Mohamad Ardin Suwandi (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2024)
The aim of this research is to analyze the implementation of Teacher Professional Education in improving the professionalism of PAI Teachers and analyze the supporting and inhibiting factors for PAI Teachers at SD Negeri 2 Jragan, Tembarak District, participating in Teacher Professional Education. This research method uses a qualitative method with a pedagogical approach, and a type of field research. The results of this research are as follows. First, the Professional Teacher Education program can improve the professionalism of PAI Teachers, as evidenced by the PAI Teacher Performance Assessment before PAI Teachers took Professional Teacher Education getting a score of 79.98. Meanwhile PAI teachers who have taken Teacher Professional Education received a score of 81.23. After PAI Teachers participated in Professional Teacher Education and received professional allowances, most PAI Teachers have succeeded in developing themselves by achieving teacher competencies which consist of 5 competencies. This shows that PAI teachers can teach well, have good personalities, socialize well, and carry out their duties as professional teachers with full responsibility. Second, supporting factors for PAI teachers implementing Professional Teacher Education, include: support from various parties, receiving facilities from the school, colleagues who help with various Professional Teacher Education activities, competent lecturers at LPTK UIN Salatiga, and LPTK concern UIN Salatiga. Meanwhile, inhibiting factors include: limited time, uncertain Professional Teacher Education schedules from lecturers, boredom because work outside of Professional Teacher Education sometimes coincides with Professional Teacher Education activities, responsibilities as a teacher that must continuing to teach, the laptop used sometimes suddenly goes blank, it is hampered when recording the Comprehensive Examination due to lack of skills in using Information and Communication Technology (ICT).